Predictors of practices on Zika virus infection among women attending antenatal care at public clinics in Johor Bahru district 2017 - Ahmad, Mohd Anwar Shahrir (2017)
Background: Zika Virus outbreak was announced as Public Health Emergency Of International Concern (PHEIC) in February, 2016 as sudden increasing of microcephaly cases and other neurological disorders in some areas affected by Zika Virus. Furthermore, other than transmitted via mosquito bites, some studies proven that Zika Virus infection can also be transmitted through sexual intercourse and blood-borne. In 2016, there was occurrence of two confirmed Zika Virus infection cases in Johor Bahru district, which one of them was a pregnant woman.